The analysis of the principal's leadership impact on teacher performance through teacher competence and compensation as mediator - Agie Hanggara; Cucu Suhartini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The competence of teachers is a crucial aspect that warrants increased attention in order to ensure the success of the teaching process.This study aims to determine whether teacher competence mediates the influence of the principal's leadership on teacher performance in private high schools throughout Kuningan Regency; To find out that compensation mediates the influence of the principal's leadership on teacher performance in private high schools throughout Kuningan Regency. This research is categorized as a type of quantitative research with survey techniques. The data analysis technique used is parallel multiple mediator models. And the sample used is 131 teachers in private high schools in Kuningan Regency. Based on the results of the study, it can be concluded that: Principal leadership influences teacher performance. This means that the more effective the principal's leadership, the higher the teacher's performance; Teacher competence fully mediates the influence of the principal's leadership on teacher performance in Private High Schools throughout Kuningan; Teacher compensation partially mediates the influence of the principal's leadership on teacher performance in private high schools throughout Kuningan.